IMPROVING YOUNG LEARNERS SPEAKING SKILL THROUGH ROLE-PLAY - Cendana Kriswidyanovita (Widya Mandala Surabaya Catholic University, 2022)
In improving young learners speaking skill, role-play is one of the techniques that can stimulate students to communicate with fun. The activity will stimulate students to speak English and make learning alive. Role-Play also increases motivations and develops fluency in speaking. This study aims at finding out young learners’s improvement in speaking skill through role-play. The research method was quasi-experimental using non-randomized pre-test and post-test group as her design. The writer gave two types of techniques in two different groups—Role Play in the experimental group and Presentation in the controlled one.The pretest and post-test was analyzed using t-test. The data shows a significant difference between pre-test and post-test scores among two groups.